(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2012)
The tax exemption, whether wholly or partially, and for an unlimited duration of the investment or for a limited period of few years, is one of the encouraging things to the flow of foreign capital. And if necessary, impose tax on the profits of the invested capital, the promotion requires that not be discriminatory taxes or payments in the amount of money with the need to avoid double taxation. The tax exemption is granted by the government and the feature according to the law of a natural person or legal entity seeking from the government purports to achieve a set of political goals, economic and social development. The reduction of taxes or grants partial exemption is one of the factors that encourage attract of direct foreign investment.